Epidemiology and risk factors of atopic dermatitis among children in Basrah, Iraq - Aya A. Al-Rubaye; Asaad Q. Al-Yassen (Intelektual Pustaka Media Utama, 2023)
Atopic dermatitis is a major public health problem, especially among children and has an economic burden at family and community levels. The present research aimed to study the frequency, distribution and determinants of atopic dermatitis in Basrah city, Iraq. A cross-sectional study was carried out between December 2020 and March 2021 at the dermatology outpatient clinic of Alfayhaa Hospital in Basrah, Iraq. The overall prevalence of the disease among children was 21.3 %. The age-specific prevalence rate among infantile, childhood and adolescent groups were 40.7%, 21.7%, and 12.1%, respectively. One hundred Four children who attended the dermatology outpatient clinic were diagnosed with Atopic dermatitis. The mean age of the patients was 6.6±2.8 years. In 87.5% of the cases, the onset of disease was before two years of age. Using objective scoring atopic dermatitis (SCORAD), the disease was classified into mild, moderate and severe with a percentage of 10.6, 83.6, and 5.8, respectively. There was no significant association between the severity of atopic dermatitis with early-onset, positive family history of atopy, nor a high body mass index (BMI). We recommend further large-scale and community-based studies to estimate the real burden of the disease with emphasis on preventive measures.